Performance Testing of PCR Assay in Blood Samples for the Diagnosis of Toxoplasmic Encephalitis in AIDS Patients from the French Departments of America and Genetic Diversity of Toxoplasma gondii: A Prospective and Multicentric Study. - Daniel Ajzenberg; Isabelle Lamaury; Magalie Demar; Cyrille Vautrin; André Cabié; Stéphane Simon; Muriel Nicolas; Nicole Desbois-Nogard; Rachida Boukhari; Homayoun Riahi; Marie-Laure Dardé; Patrice Massip; et al. (Public Library of Science (PLoS), 2016)
Toxoplasmic encephalitis in patients with AIDS is a life-threatening disease mostly due to reactivation of Toxoplasma gondii cysts in the brain. The main objective of this study was to evaluate the performance of real-time PCR assay in peripheral blood samples for the diagnosis of toxoplasmic encephalitis in AIDS patients in the French West Indies and Guiana.Adult patients with HIV and suspicion of toxoplasmic encephalitis with start of specific antitoxoplasmic therapy were included in this study during 40 months. The real-time PCR assay targeting the 529 bp repeat region of T. gondii was performed in two different centers for all blood samples. A Neighbor-Joining tree was reconstructed from microsatellite data to examine the relationships between strains from human cases of toxoplasmosis in South America and the Caribbean. A total of 44 cases were validated by a committee of experts, including 36 cases with toxoplasmic encephalitis. The specificity of the PCR assay in blood samples was 100% but the sensitivity was only 25% with moderate agreement between the two centers. Altered level of consciousness and being born in the French West Indies and Guiana were the only two variables that were associated with significantly decreased risk of false negative results with the PCR assay.Our results showed that PCR sensitivity in blood samples increased with severity of toxoplasmic encephalitis in AIDS patients. Geographic origin of patients was likely to influence PCR sensitivity but there was little evidence that it was caused by differences in T. gondii strains.ClinicalTrials.gov NCT00803621.